The impact of Irish budgetary policy by disability status - Karina Doorley; Mark Regan (The Economic and Social Research Institute (ESRI), 2022)
Existing research has shown that disability is costly and can result in an increased risk of living in poverty and a decrease in living standards. In this paper, we expand a framework of equality budgeting, previously applied from a gender perspective, to the population of households affected by disability. Using a microsimulation model linked to data from the EU Survey of Income and Living Conditions (EU-SILC), we show how tax-benefit policy and other market income changes between 2007 and 2019 impacted households affected by disability and households not affected by disability. We find that disposable (or post-tax and transfer) income grew for both types of households but at a faster rate for households affected by disability than households not affected by disability. This income growth was driven by two counteracting forces. On the one hand, tax and welfare policy failed to keep pace with market income growth, reducing the living standards of households affected by disability by more than households not affected by disability. On the other hand, despite having lower average wage levels, wage growth for workers affected by disability outpaced wage growth for workers not affected by disability, while the labour supply of households affected by disability also increased. Future attempts to equality-proof budgetary policy should consider that changes to welfare disproportionally affect households with disabilities.
Keywords: 330